ANALISIS KUALITAS AIR TANAH DI PETOBO - Putri Hasanah; Irwan Said (Universitas Tadulako, 2020)
The purpose of this study was to determine groundwater quality based on parameters of pH, COD, and BOD levels. These parameters are in accordance with Government Regulation No. 82 the year 2001 that concern the management of water quality and control of water pollution. pH meter was used for pH measurement. For COD concentration, the titrimetric titration was used while the iodometric titration for BOD concentrations. The results showed that the pH value of water was 7.9, the COD level was 7.84 mg/L and the BOD level was 1.68 mg/L. According to Government Regulations No. 82 the year 2001, it states that the level of COD based on its class is 10 mg/L (class I), and BOD based on its class is 2 mg/L. Therefore, the result of the COD and BOD concentrations are below of class 1 standards, it means the groundwater quality for two parameters in the Petobo area is still suitable for daily use.